Re-examination of the Khar khoroot inscription
The inscriptions of Khar Khoroot, Bayanbürd Bag, Buutsagaan Sum, Bayankhongor Province, were re-examined. A few characters and letters were inadvertently copied. There is a single line of inscription in the Khar Khoroot that says, yätmis apa on bašï bitidim I, the corporal, wrote for Yetmish Apa”. Except for Khar Khoroot, none of the Mongolian runic monuments have intentionally drawn boundaries. The inscription on Khar Khoroot is unique in this regard. Upon the demise of a nobleman named Yätmis Apa, an inscription was crafted in his honor. The framing of the inscription might serve as a symbolic indication of its intended purpose for a funeral. Depicting deceased individuals through the use of frames and fences is a prevalent practice in human societies, serving as a universal emblem and symbol throughout cultures. Put simply, Yetmish Apa, who died while traveling, was unable to construct a sacrificial complex due to lack of chance or time. As a result, they were burned, and a commemorative inscription was made. The absence of any other stamp associated with the Turkic and Uighur periods on the Khar Khoroot rock indicates that the scribes had a brief presence and only inscribed on specific occasions. Chronologically, it is clear that the Khar Khoroot inscription belongs to the Uighur period. Хар хороотын бичээсийг нягтлахад Товчлол. Баянхонгор аймгийн Бууцагаан сумын Баянбүрд багийн нутаг Хар хороотын бичээсийг дахин нягталлаа. Зарим үсэг тэмдэгтийг ташаарч хуулснаас судалгаа мадагтай болсон байна. Хар хороотод m